Implementation of Task-Based Language Teaching Methods to Improve Students' Speaking Skills - Rahmiati; Husnani Aliah; Puspa Sari (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study evaluates the effectiveness of the Task Based Language Teaching (TBLT) Method in improving the speaking ability of second grade students of SMA Negeri 6 Palopo. Task Based Language Teaching is an English language learning approach that uses tasks as the core unit of planning and teaching. In TBLT, students are required to understand the learning material that has been delivered by the teacher, then complete tasks that aim to encourage the use of the target language. This study uses a quasi-quantitative experimental method with data collection techniques in the form of pre-tests and post-tests. The research sample was selected randomly from the student population. The results showed that there was a statistically significant difference between the experimental class using the TBLT Method and the control class using the conventional method based on the results of the independent T-test. Significant improvements were seen in the "Very Good" and "Moderate" categories in the experimental group compared to the control group. Student motivation factors also influenced the results of this improvement.